Understanding national identity. - McCrone, David (Cambridge University Press, 2015)
We live in a world in which being a 'citizen' of a state and being a 'national' are by no means the same. Amidst much scholarly debate about 'nations' and 'nationalism', comparatively little has been written explicitly on 'national identity' and a great deal less is solidly evidence-based. This book focuses on national identity in England and Scotland. Using data collected over twenty years it asks: does national identity really matter to people? How does 'national identity' differ from 'nationality' and having a passport? Are there particular people and places which have ambiguous or contested national identities? What happens if someone makes a claim to a national identity? On what basis do others accept or reject the claim? Does national identity have much internal substance, or is it simply about defending group boundaries? How does national identity relate to politics and constitutional change? -- Présentation de l'éditeur.